2007
DOI: 10.1002/arch.20194
|View full text |Cite
|
Sign up to set email alerts
|

The effects of boric acid‐induced oxidative stress on antioxidant enzymes and survivorship in Galleria mellonella

Abstract: Larvae of the wax moth, Galleria mellonella (L.), were reared from first instar on a diet supplemented with 156, 620, 1,250, or 2,500 ppm boric acid (BA). The content of malondialdehyde (MDA, an oxidative stress indicator), and activities of the antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), and glutathione peroxidase (GPx)] were determined in the fat body and hemolymph in the 7th instar larvae and newly emerged pupae. Relative to control larvae, MDA was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 30 publications
8
55
0
Order By: Relevance
“…Plants sprayed with boron and zinc chelates lowered the incidence of leaf folder as earlier reported by Premila et al, (1984). Hyrsl et al, (2007) reported that boric acid has adverse effect on survival, development and fecundity of insects. Hence, the present finding is well supported by above findings.…”
Section: Effect Of Fertilizers Fertilizer Combinations and Manure Onsupporting
confidence: 70%
“…Plants sprayed with boron and zinc chelates lowered the incidence of leaf folder as earlier reported by Premila et al, (1984). Hyrsl et al, (2007) reported that boric acid has adverse effect on survival, development and fecundity of insects. Hence, the present finding is well supported by above findings.…”
Section: Effect Of Fertilizers Fertilizer Combinations and Manure Onsupporting
confidence: 70%
“…Enzyme extraction in whole body of larvae was made according to methods of İcen et al (2005) and Hyršl et al (2007). All larvae were in the same chronological age.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…In Galleria mellonella, boric acid has an impact on its immunocompetence (Durmus and Büyükgüzel 2008) and on its oxidative stress management (Hyrsl et al 2007). …”
Section: Introductionmentioning
confidence: 99%